Sexual and reproductive health experiences, access to services, and sources of information among university students in Ethiopia - Chekol, Bekalu Mossie; Sheehy, Grace; Siraneh, Yibeltal (Frontiers in Reproductive Health, 2023)
Adolescence and youth are times of major growth and change that can place young people at elevated risk of poor sexual and reproductive health (SRH) outcomes, particularly when they are living away from home for the first time. Understanding the barriers that young people face when accessing SRH services and information is imperative for addressing their SRH needs; our study explored this topic among university students in Ethiopia. Specifically, we explore university students' SRH experiences, access to services, and preferred sources of information. We draw on mixed-methods research conducted in four public universities across Ethiopia in early 2020. A random sample of 822 male and female students completed a cross-sectional survey that explored SRH knowledge, attitudes, experiences, and sources of information. We also conducted 8 focus group discussions with students and 8 key informant interviews across the four universities. Survey data were analyzed using descriptive statistics and we used structural coding and inductive analysis to analyze qualitative data. The survey data demonstrated that condoms and emergency contraceptive pills were the most used contraceptive methods. Nearly 18% of female students had experienced an unwanted pregnancy, and 14% reported having had an abortion. Approximately one-third of students reported encountering gender-based violence in the past 6 months. Most students preferred receiving SRH information from mass media, and male students were more likely than female students to seek information from friends. Our qualitative findings highlight a lack of comprehensive SRH care available on university campuses, and services that are available are often of poor quality; participants described a lack of privacy, confidentiality and respect when accessing SRH care at school. University students also lack regular opportunities to learn about SRH while on campus, and their preferred sources of information varied widely. Ethiopian university students have considerable unmet demand for SRH services and often face significant barriers to accessing high-quality information and services on campus. Consistent commitment and investment by universities and the government is vital to meeting the SRH needs of young people during this potentially vulnerable time.